Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Fisik, dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Steven Virgus Yudistira; Patrick Heaven; Antonius Kristian; Jonathan Widarta Wijaya (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of leadership style, work environment, and work motivation on employee job satisfaction in minimarkets. In the context of increasingly fierce business competition, companies are required to enhance service quality and customer satisfaction, which heavily relies on employee satisfaction. The research method employed is quantitative, with data collection conducted through a Likert scale-based questionnaire. The sample consists of 100 respondents who are employees of minimarkets. Data analysis is performed through validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that work motivation has a positive and significant effect on employee job satisfaction, supporting the proposed hypothesis. Additionally, normality and multicollinearity tests show that the data used are suitable for further analysis. This research provides important insights for management in designing effective strategies to enhance employee job satisfaction, which in turn can positively impact overall company performance. Thus, effective human resource management becomes key to achieving organizational goals in this era of globalization.